Serpenteando: experienciando a construção de um espaço de divulgação científica sobre o ofidismo - Lima, Camila do Nascimento Moreira (Universidade Federal de São Carlos, 2022)
Snakes are among the most fearsome animals and this happens because this group has a socially constructed stigma (even in the religious view) of being cunning, treacherous and vengeful, in addition, they still have some venomous species. In the last 30 years, due to human actions such as urbanization and agriculture, snakes have lost about 80% of their habitat in the national territory. The consequence of this process is the entry of these animals into urban spaces in search of shelter and resources to survive. This leads to a higher probability of accidents in areas close to rural areas. In these places, residents may not be used to living with wild animals, at the risk of suffering an ophidian accidents or killing the snake. From these questions, the idea of ​​this work is to create a scientific popularization blog that addresses the themes of snakes and snakes topics, aiming to improve the coexistence between residents who live close to rural areas with the snakes in the surroundings. In this blog, basic knowledge about snakes is found, the importance of this group is emphasized and it is expected to provide access to the snakes topics debate and snake preservation. The blog is composed of articles, which were defined according to the author's perception (who lives in an area that fits the presented context) about the need for information in the face of doubts that arose among the neighbors. The site was created using the WordPress tool and made available remotely through GitHub Pages and has the title: "Serpenteando - A mini guide to coexistence".
Slide like snakes: experiencing the production of a space for scientific dissemination about snakes topics.
Keywords: Divulgação científica; Relato de experiência; Serpentes; Conservação; Scientific dissemination; Experience report; Snakes; Conservation; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO